First synthesis of cryptands with sucrose scaffold - Sokołowska, Patrycja; Kowalski, Michał; Jarosz, Sławomir (Beilstein Journal of Organic Chemistry, 2019)
Cryptands with sucrose scaffold, an unknown class of such derivatives, were prepared from the readily available 2,3,3’,4,4’-penta-O-benzylsucrose and 1’,2,3,3’,4,4’-hexa-O-benzylsucrose.
Keywords: cryptands; macrocyclization; sucrose